Analysis of Environmental Quality Changes of Citarum Watershed of West Java and their Effects on Operational Costs of Hydroelectric Power Plans and the Regional Drinking Water Companies (Case Study at Saguling, Cirata, and Jatiluhur Hydroelectric Power Pl - RADJAB TAMPUBOLON; B. SANIM; M. SRI SAENI; R. BOER (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2007)
The objectives of this research were to analyze land cover changes, hydrological characteristics changes, and their effects on the economic value of water resources for environmental services beneficiaries (Hydroelectric Power Plan, HEPP and Drinking Water Companies, DWC). This research was conducted from January to December 2006 in the upper Citarum watershed, covering the Saguling, Cirata, and Jatiluhur catchments, with total area of 486,237 ha. The economic actors under this study are Saguling HEPP, Cirata HEPP, and Jatiluhur HEPP as well asTirta Dharma DWC (Purwakarta) and PT Thames Jaya DWC (Jakarta) which are located downstream of Citarum watershed as the beneficiaries of environmental services of Citarum watershed. The methodology and analysis technique used in this research were : a) supervised classification analysis to find out land cover changes; b) GR4J model to predict water discharge, water volume, and sedimentation; and c) water chemical analysis and replacement cost method for economic valuation of environmental services among the beneficiaries (HEPP, DWC). The resultsshowed that during the 1992 to 2002 period, there has been a reduction of forest (tree) area at the rate of 2.23% (3,804.2 ha) annually. The reduction of forest area was mainly caused by increasing of land clearing for settlement and other infrastructure which grew at the rate of 9.81% (2,404.5 ha) annually. This landuse change has influenced on hydrological characteristics of the upper Citarum watershed as shown by the reduction of local water discharge as high as 1.49% (3.14 m3 sec-1) and the volume of local water input as high as 4.20% (275.26 million m3), the increasing ratio of Qmax/Qmin as high as 5.99% (at the average of 131.94), the increasing of sediment yield as high as 10.20 to 12.86 million m3 annually (for the three dams) which is very dangerous, especially for Saguling and Cirata dams, as well as the decreasing of chemical water quality of Citarum River. Landuse and hydrological characteristics changes has caused an economic loss (opportunity cost) among the HEPPs and DWCs. The amount of the opportunity cost due to environmentaldegradation of upper Citarum watershed suffered by the HEPPs was as high as Rp 43.44 billion (equivalent with Rp 9,538,- MWh-1 electricity or Rp 3.29 m-3 water used by HEPP). Whereas economic lost suffered by DWC were Rp 212.43,- m-3 (Purwakarta DWC) and Rp 821.48 m-3 (Jakarta DWC) respectively. Based on significant economic loss caused byenvironmental degradation of the upper Citarum watershed on HEPP and DWC, the efforts for controlling landuse allocation and soil conservation seem very necessarily, by assigning permanent forest cover area. The amount as reflected by opportunity cost could be used as environmental investment for improving environmental quality (replacement cost) in the upper Citarum watershed.